Pengaruh Profitabilitas dan Kualitas Pengungkapan Corporate Social Responsibility terhadap Harga Saham - Triani, Triani; Amiin, Siti Nur (STIE Widya Manggala, 2019)
This study aims to determine the effect of Earning Per Share (EPS), Return On Equity (ROE) and Quality of CSR on LQ 45 Company Stock Prices on the Indonesia Stock Exchange in 2015-2017. The population of this study was 45 companies and the sample was 36 LQ 45 companies listed on the Indonesia Stock Exchange for the period 2015-2017. The method of analysis uses classical assumption test calculations and analysis tools using multiple linear regression with SPSS software. Partial results show that Earning Per Share (X1) and Return On Equity (X2) have a significant influence on stock prices, while the quality of CSR (X3) does not affect stock prices. Simultaneously test all Earning Per Share (EPS), Return On Equity (ROE) and Quality of CSR have an effect on the Stock Price of LQ 45 companies listed on the Indonesia Stock Exchange in 2015-2017.